1958
DOI: 10.1136/thx.13.3.213
|View full text |Cite
|
Sign up to set email alerts
|

The Aetiology of Pulmonary Thrombosis in Cyanotic Congenital Heart Disease with Pulmonary Stenosis

Abstract: Although a decade has passed since Rich (1948) reported the tendency of pulmonary thrombosis to develop in patients with Fallot's tetralogy, the aetiological factors concerned in this process have received little attention. He considered the classical pathological causes of thrombosis, namely anoxaemia, diminished pulmonary blood flow and increased blood viscosity, to be more important than pulmonary embolism, but he gave no physiological data to support this view. The purpose of this communication is to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1959
1959
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Heath et al [15], especially, demonstrated that pulmonary thrombi are present only when the pulmo nary index (pulmonary blood flow in litres per minute per square metre of body surface) is less than 2.5. Compensatory polycythemia increases the tendency to thrombosis, by increasing blood viscosity [24,1,15], without being however an indispensable factor. Moreover, a correlation of no small practical importance has been shown between the occurrence of thrombi and the patients age [23.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heath et al [15], especially, demonstrated that pulmonary thrombi are present only when the pulmo nary index (pulmonary blood flow in litres per minute per square metre of body surface) is less than 2.5. Compensatory polycythemia increases the tendency to thrombosis, by increasing blood viscosity [24,1,15], without being however an indispensable factor. Moreover, a correlation of no small practical importance has been shown between the occurrence of thrombi and the patients age [23.…”
Section: Discussionmentioning
confidence: 99%
“…This is considered the main and most effective cause of pulmonary thrombosis in congenital heart disease with pulmonary stenosis or atresia [7,22,9]. Heath et al [15], especially, demonstrated that pulmonary thrombi are present only when the pulmo nary index (pulmonary blood flow in litres per minute per square metre of body surface) is less than 2.5. Compensatory polycythemia increases the tendency to thrombosis, by increasing blood viscosity [24,1,15], without being however an indispensable factor.…”
Section: Discussionmentioning
confidence: 99%